2012
DOI: 10.1038/jcbfm.2012.55
|View full text |Cite
|
Sign up to set email alerts
|

Immune Effects of Mesenchymal Stromal Cells in Experimental Stroke

Abstract: Preclinical trials confirmed the potential of mesenchymal stromal cells (MSCs) to improve functional recovery after experimental stroke. Beneficial effects of MSCs are often attributed to their immunosuppressive/immunomodulatory functions. Surprisingly, the influence of MSCs on the immune system after stroke is poorly understood, but requires special consideration because cerebral ischemia is associated with stroke-induced immunodepression that predisposes to bacterial infections with increased mortality. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 37 publications
0
30
0
1
Order By: Relevance
“…Although experimental studies have proven stroke-induced immunodepression by showing decreased peripheral IL-6 production, numerous clinical studies have found that IL-6 expression actually increases after stroke in response to strong inflammatory reactions induced by ischaemic brain injury [2830]. Our results suggest that very strong inflammatory responses occur in SAI patients which activate anti-inflammatory feedback causing increased IL-10.…”
Section: Discussionmentioning
confidence: 63%
“…Although experimental studies have proven stroke-induced immunodepression by showing decreased peripheral IL-6 production, numerous clinical studies have found that IL-6 expression actually increases after stroke in response to strong inflammatory reactions induced by ischaemic brain injury [2830]. Our results suggest that very strong inflammatory responses occur in SAI patients which activate anti-inflammatory feedback causing increased IL-10.…”
Section: Discussionmentioning
confidence: 63%
“…Scheibe et al raised the question of possible deleterious effects of MSCs on the immune response in stroke in view of the strokeinduced immunodepression associated with cerebral ischemia, which predisposes to bacterial infections with increased mortality. Despite their immunosuppressive effects in vitro, transplantation of MSCs in mice after MCAO did not affect the serum levels of relevant inflammatory cytokines, suggesting that safety concerns for MSC transplantation in stroke are likely to be unwarranted [124].…”
Section: Ischemic Strokementioning
confidence: 92%
“…[1][2][3][4][5] Due to their origin, bone marrow-derived stem cells are less debated from an ethical point of view than embryonic stem cells (ESCs). MSCs can differentiate into a number of mesenchymal phenotypes, including adipocytes, osteocytes, chondrocytes, and myocytes.…”
Section: Introductionmentioning
confidence: 99%